How can the integration of EAL students into mainstream English and its effects on the student be managed to optimize academic achievement? : Moving on to closing the gap - Pantasoulas, Maria (2016)
This research attempts to see how the challenges faced by EAL students entering mainstream English can be managed in order to optimise academic achievement of such students and assist them in becoming proficient in academic English. It is hoped that an understanding of particular difficulties will be achieved through which teaching strategies and areas of development might be put into place in these classrooms. The research takes place in an international school with a diverse mix of nationalities and within the researcher’s own Year 7 English class. Over the course of four and a half weeks it examines how a writing unit on ‘Superheroes’ specifically incorporating techniques which provide better support for English learners will allow students to accomplish the learning objective of writing a superhero short story. The research underlying this writing unit raises the more specific questions: a) Can incorporating teaching techniques proven to be beneficial for L2 learners raise attainment of lesson content? b) What specific challenges do L2 learners face when writing?